Respons Pertumbuhan Bibit Tanaman Kakao (Theobroma cacao L.) Terhadap Pemberian Biochar Sekam Padi dan Mikoriza pada Tanah Ultisol - Febianus Sapitu; Rista Delyani; Zaenal Mutaqin; Nober Padidi (AGRORADIX : Jurnal Ilmu Pertanian, 2025)
The availability of ultisol soil, in the form of red-yellow podzolic soil, is essential in increasing cocoa production, especially in crop cultivation to meet national cocoa needs. This study aims to assess the effect of rice husk biochar and mycorrhiza, and the interaction of the two treatments on the growth of cocoa seedlings on red-yellow podzolic (ultisol) soil. This study used a quantitative method using Factorial Randomized Block Design (RBD), with 3 blocks as replicates. The first factor is the dose of rice husk biochar consisting of four levels, namely 0 t ha-1 (B0), 10 t ha-1 (B1), 20 t ha-1 (B2), and 30 t ha-1 (B3). The second factor was the dose of mycorrhiza with 4 levels, namely 0 g polybag-1 (M0), 12.5 g polybag-1 (M1), 25 g polybag-1 (M2), and 37.5 g polybag-1 (M3). The data were analyzed using Analysis of Variance and followed by the Post Hoc Tukey’s HSD at α= 5%. The results showed that the application of rice husk biochar at a dose of 30 t ha-1 gave the best results and significantly affected the plant height and crown wet weight of cocoa seedlings compared to the control. In addition, the application of mycorrhiza at a dose of 37.5 g polybag-1 also gave the best results and significantly affected plant height, stem diameter, crown wet weight, and crown dry weight of cocoa plant seedlings compared to the control. However, the interaction between the two treatments did not significantly affect each variable observed.